Derivation of Human Differential Photoreceptor-like Cells from the Iris by Defined Combinations of CRX, RX and NEUROD - Seko, Yuko; Azuma, Noriyuki; Kaneda, Makoto; Nakatani, Kei; Miyagawa, Yoshitaka; Noshiro, Yuuki; Kurokawa, Reiko; Okano, Hideyuki; Umezawa, Akihiro (PLOS ONE, 2012)
Examples of direct differentiation by defined transcription factors have been provided for beta-cells, cardiomyocytes and neurons. In the human visual system, there are four kinds of photoreceptors in the retina. Neural retina and iris-pigmented epithelium (IPE) share a common developmental origin, leading us to test whether human iris cells could differentiate to retinal neurons. We here define the transcription factor combinations that can determine human photoreceptor cell fate. Expression of rhodopsin, blue opsin and green/red opsin in induced photoreceptor cells were dependent on combinations of transcription factors: A combination of CRX and NEUROD induced rhodopsin and blue opsin, but did not induce green opsin; a combination of CRX and RX induced blue opsin and green/red opsin, but did not induce rhodopsin. Phototransduction-related genes as well as opsin genes were up-regulated in those cells. Functional analysis; i.e. patch clamp recordings, clearly revealed that generated photoreceptor cells, induced by CRX, RX and NEUROD, responded to light. The response was an inward current instead of the typical outward current. These data suggest that photosensitive photoreceptor cells can be generated by combinations of transcription factors. The combination of CRX and RX generate immature photoreceptors: and additional NEUROD promotes maturation. These findings contribute substantially to a major advance toward eventual cell-based therapy for retinal degenerative diseases.